Haplomesus longiramus sp. nov. (Crustacea: Isopoda: Asellota), a new ischnomesid species from the Bay of Biscay, North East Atlantic Ocean - Kavanagh, Fiona A.; Sorbe, Jean-Claude (Zootaxa, 2006)
A new species of Ischnomesidae (Crustacea: Isopoda: Asellota), Haplomesus longiramus sp. nov. is described from the Bay of Biscay. This species is unusual due to the presence of long, thin anterolateral projections supporting the antennae and an elongate pereonite 4. These features are also seen in Haplomesus biscayensis Chardy, 1975, and the two species closely resemble each other. The presence of a laterally directed spine on pereonite 5 of the male of Haplomesus longiramus sp. nov. along with the elongate uropods of both male and female easily differentiates this species from H. biscayensis. Within its known distributional area, this new Haplomesus species inhabits bathyal muddy bottoms from 500–1009 m, with a maximum abundance of 29 individuals per 100 m 2 recorded at approximately 700 m.